Arabidopsis synaptotagmin SYTA regulates endocytosis and virus movement protein cell-to-cell transport - Lewis, Jennifer D. (National Academy of Sciences, 2010)
Synaptotagmins are calcium sensors that regulate synaptic vesicle exo/endocytosis. Thought to be exclusive to animals, they have recently been characterized in plants. We show that Arabidopsis synaptotagmin SYTA regulates endosome recycling and movement protein (MP)-mediated trafficking of plant virus genomes through plasmodesmata. SYTA localizes to endosomes in plant cells and directly binds the distinct Cabbage leaf curl virus (CaLCuV) and Tobacco mosaic virus (TMV) cell-to-cell movement proteins. In a SYTA knockdown line, CaLCuV systemic infection is delayed, and cell-to-cell spread of TMV and CaLCuV movement proteins is inhibited. A dominant-negative SYTA mutant causes depletion of plasma membrane-derived endosomes, produces large intracellular vesicles attached to plasma membrane, and inhibits cell-to-cell trafficking of TMV and CaLCuV movement proteins, when tested in an Agrobacterium-based leaf expression assay. Our studies show that SYTA regulates endocytosis, and suggest that distinct virus movement proteins transport their cargos to plasmodesmata for cell-to-cell spread via an endocytic recycling pathway.